Knowledge and practices relating to malaria in a semi-urban area of Cameroon: choices and sources of antimalarials, self-treatment and resistance - Nsagha, Dickson Shey (The African Field Epidemiology Network, 2011)
INTRODUCTION: Malaria is a major public health problem in Sub-Saharan Africa where it kills a child under the age of five every 30 seconds. In Cameroon, malaria accounts for 40–45% of medical consultations, 57% of hospitalization days and 40% of mortality among children below 5 years. Community knowledge and practices can enhance the fight against this disease. The aim of the study was to make a local analysis of the people's knowledge and practices relating to the choice and source of antimalarials, self-medication, malaria dosage and resistance in order to establish behavioural baseline and epidemiological determinants and their implications for malaria control. METHODS: The design was a community-based cross-sectional study in a semi-urban setting. The survey consisted of 253 volunteer participants (from among 350 contacted) from different socio-demographic backgrounds to whom structured questionnaires were administered. The respondent's consent was sought and gained and subjects who could not read or write or understand English language were communicated to in the local language. The questionnaire was administered by trained interviewers according to the schedule of the respondent. The data was analysed using SPSS. RESULTS: Antimalarials commonly cited for malaria treatment were chloroquine (26.1%) and nivaquine (14.6%) and analgesics: panadol (23%) and paracetamol (12.3%) including native drugs (6.3%). 141(55.7%) (95% confidence interval (CI): 49.6–61.8%) participants practiced self-medication of malaria. 26.1% participants knew the correct adult malarial dosage for chloroquine or nivaquine. 125(40.4%) (95% CI: 34.4–46.7%) participants got their antimalarials from health centers, 27(10.6%) from shops, 24(9.5%) from hawkers, 23(9.1%) from the open market and 16 (6.3%) from herbalists. 66 (26.1%) (95% CI: 20.7–31.5%) participants knew the correct adult dosage for chloroquine or nivaquine treatment of malaria. 85(33.6%) (95% CI: 27.8–36.6%) participants had correct knowledge of malarial resistance. Of the 85 (33.6%) participants who had correct knowledge of antimalarial drug resistance, 52(20.6%) ascribed antimalarial drug resistance to continuous fever for a long time during treatment, 15 (5.9%) to serious fever during treatment and 18 (7.1%) when chloroquine does not stop fever. 23(27.1%) participants with correct knowledge of malarial resistance were in the 31–35 age group bracket compared with other age groups (P=0.1). There was a significant difference in correct knowledge of malarial resistance and participant's profession (p=0.0). CONCLUSION: Malaria self-medication is common in Ndu but knowledge of antimalarial drug resistance is poor. Improvement in the self-treatment of malaria could be attained by providing clear information on choices of drugs for malaria treatment. Proper health information on the rational use of ant-malarial drugs must be provided in an appropriate manner to all groups of people in the society including village health workers, women associations, churches, school children, “Mngwah” opinion leaders, herbalists, health workers and chemists. Self-medication should be improved upon by giving correct information on the dosage of malaria treatment on radio, television, posters and newspapers because banning it will push many people to use it in hiding.